Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1176/appi.ajp.2009.08111667
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Neighborhood Environment on Treatment Continuity and Rehospitalization in Dually Diagnosed Patients Discharged From Acute Inpatient Care

Abstract: A more explicit focus on the neighborhood and community context represents an important area in psychiatry, in terms of both research and clinical practice, which can potentially enhance long-term care and treatment planning for psychiatric patients. Future research is needed to better understand the influence of the neighborhood environment to help predict important clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 8 publications
5
43
0
Order By: Relevance
“…The findings in this study are consistent with a study by Jacobson [27], who determined that the location of drug treatment facilities might increase client exposure to potential environmental relapse triggers, including neighborhood disadvantage, violence, and drug activity. In addition, this study is partly consistent with that of Stahler et al [16] that determined that participants living in areas of higher education had a reduced likelihood of readmission. Jacobson et al [15] focused on the racial disparities in the relationship between alcohol treatment programs and neighborhood dis- Table 2 -The multiple regression and stepwise-forward multiple regression for individual-and regional-level variables with the improving OTI score (n = 127).…”
Section: S62supporting
confidence: 91%
See 3 more Smart Citations
“…The findings in this study are consistent with a study by Jacobson [27], who determined that the location of drug treatment facilities might increase client exposure to potential environmental relapse triggers, including neighborhood disadvantage, violence, and drug activity. In addition, this study is partly consistent with that of Stahler et al [16] that determined that participants living in areas of higher education had a reduced likelihood of readmission. Jacobson et al [15] focused on the racial disparities in the relationship between alcohol treatment programs and neighborhood dis- Table 2 -The multiple regression and stepwise-forward multiple regression for individual-and regional-level variables with the improving OTI score (n = 127).…”
Section: S62supporting
confidence: 91%
“…In addition, Saxe et al [14] indicated that visible drug sales in poor neighborhoods presented a more serious problem than drug use. Few studies have identified neighborhood environment as a factor associated with treatment outcomes [15,16,27]. The findings in this study are consistent with a study by Jacobson [27], who determined that the location of drug treatment facilities might increase client exposure to potential environmental relapse triggers, including neighborhood disadvantage, violence, and drug activity.…”
Section: S62supporting
confidence: 89%
See 2 more Smart Citations
“…Several patient-related factors are associated with readmission risk, including poor medication adherence (1); substance use disorders (1); a diagnosis of schizophrenia, bipolar disorder, or depression (4); and comorbid medical disorders (5). Homelessness or residence in an institutional setting are social factors associated with psychiatric readmission (2), and previous hospitalizations (6), length of hospital stay (7,8), and lack of adequate postdischarge care for psychiatric and substance use disorders are system-related factors (9).…”
mentioning
confidence: 99%